FACTORS THAT AFFECT USING ASPECT NUMBERS ON STUDENTS SDN IN THE PANGKAJENE DISTRICT PANGKEP REGENCY - Samsiah, Samsiah (Universitas Negeri Makassar, 2013)
The government has implemented various efforts in order to improve the quality of education, especially in the field of basic education. The quality of education concerns many interrelated issues, including the quality of learners, the quality of educators (teachers) and other education personnel and facilities and infrastructure. At the operational level, the issue of quality of education is very pleased with the quality of teaching teachers and student learning. Based on that, the researcher is encouraged to analyze the factors influencing the mastery of the aspect of the number in the elementary school teacher in Pangkajene sub-district, Pangkep regency. This research belongs to survey research that is descriptive-correlative and explorative with population of all teachers of SD Negeri in Pangkajene Sub-district of Pangkep Regency. Sampling was done with a sample of considerations. Data obtained by using the instrument in the form of questionnaire and test about aspect of number. The data were processed using descriptive and inferential statistical analysis. The result of descriptive analysis shows that the mastery of number aspect in elementary school teacher is in low category. The results of inferential analysis indicate that the level of education, age and sex rate together affect the mastery of number aspect in elementary school teachers in Pangkajene sub-district, Pangkep regency. The results of explorative research indicate that other factors affecting the mastery of the number aspect are education and training, educational background, shift of teaching level, the role of teacher of mathematics guide, motivation and incentive for the achieving teacher